2012
DOI: 10.2174/1874944501205010028
|View full text |Cite
|
Sign up to set email alerts
|

Noise Exposure, Awareness, Practice and Noise Annoyance Among Steel Workers in United Arab Emirates

Abstract: Abstract:This cross-sectional study investigated noise annoyance, awareness and practice among the workers in two steel factories in UAE. The study involving 468 steel workers randomly selected. Noise exposure was estimated using the integrated sound level meter. A structured interview questionnaire was used to assess the noise annoyance, awareness and practice of workers towards the noise. The results showed that about 89 % of the workers exposed to a daily Leq above the permissible level which is 85 dB (A) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 12 publications
(21 reference statements)
2
4
1
Order By: Relevance
“…Similar results were found by Maisarah SZ et al 5.1% [44] Emmanuel DK et al5.5% [35], Razman MR et al 11.9% [45]. Hafiz Omer Ahmed13.2% [46], Foluwasayo EO et al 28% [47]. These studies verifies our finding that PPE use was not satisfactory among industrial workers.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Similar results were found by Maisarah SZ et al 5.1% [44] Emmanuel DK et al5.5% [35], Razman MR et al 11.9% [45]. Hafiz Omer Ahmed13.2% [46], Foluwasayo EO et al 28% [47]. These studies verifies our finding that PPE use was not satisfactory among industrial workers.…”
Section: Discussionsupporting
confidence: 89%
“…It shows severe deficiency in audiometry of the workers. Razman MR et al found at saw mill, Malaysia that 3.6% had audiometry [46]. In saw mill, Malaysia clinical monitoring was slightly better than our results but still deficient.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Also, 40% of all participants stated being highly annoyed by noise. This result is supported by Bedi 2006, Ahmed 2012and Singh et al 2009.…”
Section: Discussionsupporting
confidence: 53%
“…In the field of occupational audiology, complex interventions have not been conducted even though research widely demonstrates both the auditory and non-auditory health impacts of excessive exposure to occupational noise in the workplace [17][18][19][20]. Furthermore, the fact that HCPs are 'built from multiple interacting components, which act both independently and interdependently' [21,p.1281] from each other makes, them well suited to complex interventions.…”
Section: Nf Moroementioning
confidence: 99%